Business modeling and software design : 8th International Symposium, BMSD 2018, Vienna, Austria, July 2-4, 2018, proceedings /: 8th International Symposium, BMSD 2018, Vienna, Austria, July 2-4, 2018, proceedings. (2018) - Unknown
No abstract available